(3GSJOQGc GHf GdNTGH Ydi GdMQjQj aj ebGeGJg hGSJOQGc GHf HQj Ydjg ajeG GSJOQcg hGfJUGQg ddMQjQjs - (3CHheMeO YHO Gddg Hf HQj Hf YHO GdLHGQ GdebOSj GdfMhjs; (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj,J (B516 (3g` s ((3jMji Hf YHOGdehdi Hf CHj eMeO GHf MhdGf s)
(3ChdgG (B:s
(3hHYO(B: (3agPg MQha hbYJ aj GdebGeGJ GdJj CfSCgG CHheMeO GdbGSe Hf Ydj GdHUQj GdMQjQj fHg YdjgG GdTjN CHhYHOGddg s
(3BNQgG (B:s
(3hgPG ajef LYd GdCZGQjO LeY CZQhOI(B: (3GdCZfjI GdeWqQH ajgG, hef LYdgG LeY CZQGO aCZQGO LeY ZrQO HCZGfjgG hJWQHgG aj gPG GdZfi, hgPG eYfi UMjM dGaSGO ajg s
(3GfXQ GdLRA GdChd HQbe (B34(3, (B35 (3COH HYfhGf GdGYJQGVGJ Ydi GdebGeGJs
210 (3COH HYfhGf MhGTj GHf GdNTGH Ydi GdebGeGJ s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GSJOQGcs
Keywords: (3GdCOHs